The Psychology of Recent Nature Visits: (How) Are Motives and Attentional Focus Related to Post-Visit Restorative Experiences, Creativity, and Emotional Well-Being?. Issue 8 (October 2018) - Pasanen, Tytti P.; Neuvonen, Marjo; Korpela, Kalevi M.
The health-enhancing benefits of contact with nature have become widely recognized, but empirical studies that consider the motives and attentional focus of nature visits are lacking. These psychological qualities may partly determine why one visits natural environments and why some visits are more restorative than others. This study examined recent nature visits by Finnish survey respondents ( n = 565) via exploratory structural equation modeling. In the estimated models, motives and attentional focus explained 54% to 57% of post-visit restorativeness, 22% of creativity, and 33% to 37% of emotional well-being. Of the assessed motives, stress reduction was most strongly connected to increased restorativeness and emotional well-being. The motive to be alone showed a positive indirect—but negative direct—connection to emotional well-being. In addition, focus on oneself, the activity, and the environment were positively associated with the outcomes. The results indicate that motives and attentional focus are strongly connected to the outcomes of nature visits.